Composition and structure engineering of FeNi-based alloys for efficient electrocatalysis - Wang, Yong (Nanyang Technological University, 2023)
Traditional fossil fuels come with environmental challenges like air pollution and global warming. As these resources dwindle due to finite reserves, the urgent need for sustainable, clean, and affordable energy options becomes evident. Decarbonization efforts have notably sped up the advancement of renewable energy technologies. While solar and wind power have become more cost-competitive thanks to technological strides, their intermittent nature requires solutions for storing energy. Water electrolysis stands out as a technology capable of storing surplus electricity from renewables by splitting water into hydrogen and oxygen. This hydrogen, when used in fuel cells, generates electricity with only water vapor as a byproduct, showing promise as a green energy source. Presently, just 4% of hydrogen comes from renewable-powered electrolysis; most is from steam-methane reforming, a process emitting significant carbon dioxide. The high cost of precious metals used as electrocatalysts in electrolysis and fuel cells is the primary barrier to their widespread adoption. Seeking affordable, efficient, and durable catalyst alternatives is crucial to making these green technologies cost-effective. This thesis focuses on creating low-cost, efficient alloy-based electrocatalysts to enhance the cost-effectiveness and efficiency of these technologies. By exploring various alloys and their performance in energy systems, the research uncovers the composition-structure-property relationship, offering insights for optimizing electrocatalyst design and synthesis.